Perception of Society about Electrics Enter Countryside in Kenagarian Banai District Of IX Koto Sub-Province of Dharmasraya - Alina, Gustia - (Pendidikan Geografi, 2014)
Electrics represent requirement of fundamental to modern society, because all kinds of appliance of tekhnologi life need electrics as source of energi, among supporter equipment in societal life that is requirement of society will the source of energi, in growth a[n countryside besides aksessibilitas like other supporter facilities and basic facilities road street very required by is society that is requirement will the source of electrics energi. Target of this writing that is to get information, concerning perception of society about electrics enter countryside in make-up of society economics in Kenagarian Banai District Of IX Koto Sub-Province of Dharmasraya.This research type represent research qualitative, that is trying to lay open how perception of society about electrics enter countryside in make-up of society economics in kenagarian of Banai district of IX Koto sub-province of Dharmasraya, in seeing from 1) Society living 2) Earnings of society. Research informan is society who live in about/around Jorong Mudik Lago Kenagarian Banai District Of IX Koto Sub-Province of Dharmasraya. this Informan Research is taken by snow sampling ball that is snowball, intake of research subjek done/conducted directly and ask to subjek by rolling. Data collected with observation technique, interview, documentation, record-keeping of active participation and field of researcher. collected data in analysis and pulled by conclusion. Withdrawal of conclusion represent the part of one activity of intact configuraton. Conclusion and verification executed by during research, conclusion early having the character of diffuse and finally progressively detailed and grow on sturdily. In the event of mistake of data resulting inappropriate conclusion, hence can to reprocess through is same step.Result of research indicate that, farming to represent especial work which at most done by society before now, but after existence of electrics enter countryside in Kenagarian Banai District Of IX Koto Sub-Province of Dharmasraya society living become to increase and earnings also increase. Become to mount society economics in Kenagarian Banai District Of IX Koto Sub-Province of Dharmasraya.